The German SAVE Study: Design, selected results and future developments - Michela Coppola; Axel Börsch-Supan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Understanding how households form their long-term saving and investment decisions to shoulder risks not covered by social security systems has been of primary importance in all the countries which, like Germany, introduced major reforms to face the challenges of an aging population. This paper documents the scientific background and the design of the SAVE survey, a panel study developed in 2001 aimed at analyzing households' saving behaviour. Few selected results of particular relevance for the analysis of the private old-age provision in Germany are also presented. Ultimately, the future development of the SAVE-project is sketched. It will contribute to answer the new questions that challenge researchers as well as policymakers, after the financial crisis and now that the reforms of the social system in Germany are implemented.
Keywords: C81; D10; D14; 330